Things Are Getting Hairy: Enterobacteria Bacteriophage vB_PcaM_CBB - Buttimer, Colin; Hendrix, Hanne; Oliveira, Hugo; Casey, Aidan; Neve, Horst; McAuliffe, Olivia; Ross, R. Paul; Hill, Colin; Noben, Jean-Paul; O'Mahony, Jim; Lavigne, Rob; Coffey, Aidan (Frontiers in Microbiology, 2017)
Enterobacteria phage vB_PcaM_CBB is a ‘jumbo’ phage belonging to the family Myoviridae. It possesses highly atypical whisker-like structures along the length of its contractile tail. It has a broad host range with the capability of infecting species of the genera Erwinia, Pectobacterium and Cronobacter. With a genome of 355,922 bp, excluding a predicted terminal repeat of 22,456 bp, phage CBB is the third largest phage sequenced to date. Its genome was predicted to encode 554 ORFs with 33 tRNAs. Based on prediction and proteome analysis of the virions, 29% of its predicted ORFs could be functionally assigned. Protein comparison shows that CBB shares between 33-38% of its proteins with Cronobacter phage GAP32, coliphages PBECO4 and 121Q as well as Klebsiella phage vB_KleM_Rak2. This work presents a detailed and comparative analysis of vB_PcaM_CBB of a highly atypical jumbo myoviridae phage, contributing to a better understanding of phage diversity and biology.